Increasing Representation of Epidemiologists From Around the World in the Society for Epidemiologic Research: The Case of Mexico. Issue 11 (27th July 2022) - Jimenez, Marcia P; Gutierrez, Tonatiuh Barrientos; Soria-Contreras, Diana C; Abdel Magid, Hoda S; Kaufman, Jay S; Committee of the Society for Epidemiologic Research, on behalf of the Diversity; Inclusion
Abstract: Mexico has a population of 129 million and is considered one of the most unequal countries in the world, suffering from widespread health disparities. There is a pressing need to strengthen epidemiologic capacity in Mexico, to help solve the complex health problems the country faces and to reduce health inequities. However, the representation of Mexican epidemiologists in the largest epidemiologic society in North America is low, despite the short distance to the United States. In this commentary, we discuss the barriers to higher representation of Mexican epidemiologists within the Society for Epidemiologic Research (SER), including language barriers, costs, and regional necessities. We also discuss opportunities to expand Mexican SER representation and collaboration. Overall, we hope that this is a call towards expanding SER global participation and starting a conversation on a common agenda for epidemiologic research.